An impulse radar measurement in NE Greenland - Jonsson, Peter (Meddelelser om Grønland. Geoscience, 2001)
A snowmobile towed impulse radar measurement was used to produce detailed maps of ice-thickness in two areas, one on a local dome (the Hans Tausen ice cap), and one on an outlet glacier north thereof. A constant spatial sampling was achieved by using a device attached to the snowmobile’s odometer. The bedrock reflection was automatically detected in the majority of the data, by using digital signal processing techniques. After merging with differential GPS positions and elevations, a digital database of these parameters and the bedrock reflection times is presented as contour maps.